Adolescents at risk : prevalence and prevention - Dryfoos, Joy G. (Oxford University Press, 1990)
1. Introduction: Hypotheses and Theories. PART I: High-Risk Behavior. 2. The Setting: A Description of Adolescents in the United States. 3. Prevalence of Delinquency. 4. Prevalence of Substance Abuse. 5. Prevalence of Adolescent Pregnancy. 6. Prevalence of School Failure. 7. The Overlap in High-Risk Behaviors. PART II: Prevention Interventions. 8. Classification and Organization of Programs. 9. Prevention of Delinquency. 10. Prevention of Substance Abuse. 11. Prevention of Adolescent Pregnancy. 12. Prevention of School Failure and Dropping Out. PART III: Shaping a Strategy to Prevent High-Risk.